Evaluation of Rainfall and Temperature Conditions for a Perennial Crop in Tropical Wetland: A Case Study of Cocoa in Côte d’Ivoire - Fidèle Yoroba; Benjamin K. Kouassi; Adama Diawara; Louis A. M. Yapo; Kouakou Kouadio; Dro T. Tiemoko; Yves K. Kouadio; Ibrahim D. Koné; Paul Assamoi (Advances in Meteorology)
The rainfall and temperature conditions are evaluated for the first time during the 1989–2006 period, in six main cocoa production areas (Abengourou, Agboville, Daloa, Dimbokro, Guiglo, and Soubre) of Côte d’Ivoire using data from SODEXAM (ground-based observation) and the ex-CAISTAB. Statistical analysis shows an important sensitivity of cocoa production to rainfall conditions in all regions. It is worth noting that only the major rainy season from April to July and the rainfall amount of the little dry season from August to September affect the cocoa production for an 80% confidence level. This influence varies from one cacao production area to another. Moreover, the effects related to temperature on the cocoa yield seem to represent a smaller contribution of climate impact than those related to precipitation during the studied period. The temperature change remains in the acceptable range of values, between 25°C and 29°C, which is a favorable condition for cocoa growing. These findings are obtained despite the significant contributions from nonclimatic factors, to year-to-year variability in cocoa production.